The receptor for advanced glycation endproducts mediates podocyte heparanase expression through NF-κB signaling pathway. (15th July 2018) - An, Xiaofei; Zhang, Lin; Yao, Qiuming; Li, Ling; Wang, Bin; Zhang, Jisheng; He, Ming; Zhang, Jinan
Abstract: Heparanase degrades heparan sulfate in glomerular basement membrane (GBM) and plays an important role in diabetic nephropathy (DN). However, its regulating mechanisms remain to be deciphered. Our present study showed that the major advanced glycation endproducts (AGEs), CML-BSA, significantly increased heparanase expression in cultured podocytes and the effect was blocked by the receptor for advanced glycation endproducts (RAGE) knockdown, antibody and antagonist. In addition, NF-κB p65 phosphorylation was elevated and the increased heparanase expression and secretion upon CML-BSA could be attenuated by NF-κB inhibitor PDTC. Mechanistically, CML-BSA activated heparanase promoter through p65 directly binding to its promoter. Furthermore, the in vivo study showed that serum and renal cortex AGEs levels, glomerular p65 phosphorylation and heparanase expression were significantly increased in DN mice. Taken together, our data suggest that AGEs and RAGE interaction increases podocyte heparanase expression by activating NF-κB signal pathway, which is involved in GBM damages of DN. Highlights: RAGE mediates the increased heparanase expression induced by CML in podocytes. Activation of RAGE increases heparanase production and secretion through NF-κB pathway. RAGE up-regulate heparanase promoter activity through NF-κB p65 directly binding to heparanase promoter.